2009
DOI: 10.1080/10641260902752207
|View full text |Cite
|
Sign up to set email alerts
|

Tuna Nutrition and Feeds: Current Status and Future Perspectives

Abstract: Aquaculture is providing an ever-increasing proportion of fish in the human food basket prompting a search for new species to expand the range available to consumers. Large tunids/scombrids have long-since been a very valuable resource providing not only high quality protein, but also a rich source of the highly beneficial omega-3 (or n-3) long-chain polyunsaturated fatty acids including eicosapentaenoic and, especially docosahexaenoic acids in the human diet. Consequently, there is considerable interest world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 100 publications
0
24
1
Order By: Relevance
“…So far, a massive amount of study has been focused on n‐3 HUFA requirement of marine fish species. DHA is the main material in the phospholipids of the nerve tissues and the retina (Bell, Batty, Dick, Fretwell, Navarro & Sargent ; Koven ; Mourente & Tocher ), and also, it is known to play an important role in marine fish growth (Wu, Ting & Chen ). Numerous studies have reported that more DHA is needed than EPA as an essential fatty acid for growth in marine species (Watanabe, Izquierdo, Takeuchi, Satoh & Kitajima ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, a massive amount of study has been focused on n‐3 HUFA requirement of marine fish species. DHA is the main material in the phospholipids of the nerve tissues and the retina (Bell, Batty, Dick, Fretwell, Navarro & Sargent ; Koven ; Mourente & Tocher ), and also, it is known to play an important role in marine fish growth (Wu, Ting & Chen ). Numerous studies have reported that more DHA is needed than EPA as an essential fatty acid for growth in marine species (Watanabe, Izquierdo, Takeuchi, Satoh & Kitajima ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, n-3 PUFA are important for somatic growth of marine fish with DHA the most highly retained PUFA in a variety of species (Sargent et al, 2002). Tuna tissues consistently contain relatively high levels of DHA resulting in high DHA:EPA ratios (Mourente et al, 2002;Mourente and Tocher, 2009). In the present study, DHA:EPA ratios were significantly greater in gonads (approx.…”
Section: Lipid Content Class and Total Lipid Fatty Acid Compositionmentioning
confidence: 99%
“…Tuna species are considered unique as they contain high levels of DHA and very high DHA/EPA ratios (Mourente and Tocher, ). The muscles of the young or adult tunas living around Japan showed DHA levels ranging from 25% to 36% (bluefin tuna) (Ishihara and Saito, ), 22% to 36% (yellowfin tuna) (Saito et al, ), 24% to 30% (albacore Thunnus alalunga ) (Murase and Saito, ), and 28% to 34% (bonito Euthynnus pelamis ) (Watanabe et al, ) of the total fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Although Pacific bluefin tuna ( Thunnus orientalis ), yellowfin tuna ( Thunnus albacares ) and skipjack tuna ( Katsuwonus pelamis ) are important species in aquaculture for marine foods (Mourente and Tocher, ), complete knowledge on the biochemical components of wild tuna larvae is not understood to date. Morais et al () suggested adequate provision of DHA is essential for normal development of farmed Atlantic bluefin tuna larvae ( Thunnus thynnus ).…”
Section: Introductionmentioning
confidence: 99%